Dampak Konsumsi Energi Terbarukan Terhadap Ketimpangan Pendapatan di Negara-Negara OIC (Organisation of Islamic Cooperation) - Ja’far Ismail,; Ries Wulandari, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to investigate whether renewable energy consumption has an impact on income inequality in OIC countries. This study also wants to prove whether the Kuznets curve hypothesis applies in OIC countries. This analysis uses annual data from 1999 to 2020 in 20 OIC member countries and the PMG ARDL method in analyzing data with the help of Eviews 13. The results of the study show that in the long run, renewable energy consumption has a significant positive relationship with income inequality. This finding is different from previous studies which stated that renewable energy consumption has a negative relationship with income inequality. Because the results show a positive relationship between GDP growth and income inequality and a negative relationship between squared GDP growth and income inequality, it is proven that the Kuznets curve applies in OIC countries. This study also uses control variables, namely carbon emissions and zakat levels. Carbon emissions have a significant positive relationship with income inequality. The zakat level also has a positive relationship with income inequality with a significance level of 1%.